Analysis of the Influence of Physical Facility, Executive Staff, Information and Finance on the Satisfaction of Outpatient Health bpjs Participants at rsu Prima Husada Sidoarjo - Setiyaningrum, Erna; Indasah, Indasah; Farida, Siti; Maharjan, Kailie; Mark, Elladdadi (Journal of World Future Medicine, Health and Nursing, 2023)
Social security is a type of service provided by the government to the community based on the state's ability and capability to give assistance and convenience to the community. Since January 1, 2014, the Ministry of Health of the Republic of Indonesia has established Badan Penyelenggara Jaminan Sosia (BPJS) to optimise the JKN programme. BPJS is a legal company founded to organise health insurance. There are numerous programmes under the guarantee programme, including health insurance programmes, accident insurance programmes, old age insurance programmes, and death insurance programmes. The aim of this study is to examine at the influence of physical facilities, executive staff, information, and finances on outpatient BPJS Health patient satisfaction at Jagir Surabaya Health Centre. This study takes a quantitative method. This study's strategy included multiple linear regression. The individuals investigated were 90 patients recruited from the Prima Husada Sidoarjo Hospital using a proportionate random sample technique. According to the study's findings, 47.7% of physical facilities, 13.4% of implementing staff, 25.2% of information, and 24.9% of money at Prima Husada Hospital had an impact on BPJS Health patient satisfaction. The hospital's function is expected to try to improve management, particularly health management, in order to manage better.